Molecular Dynamics simulation of polymeric systems - Badur, Bertan Yılmaz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1992., 1992)
In this thesis, the dynamic and static properties of a polymeric chain in a dilute solution was investigated with the method of molecular dynamics (MD) simulation. We investigated both the equilibrium properties of polymer chains in dilute solution, such as the end-to-end distance, the radius of gyration and the radial distribution functions related to non-bonded pair correlations, and the dynamic properties of the chain such as the center of mass velocity, the orientational autocorrelation functions and the diffusion coefficient. A single oligomeric chain of 12 beads in a solvent is considered. The quality of the solvent is modified by proper modification of the polymer-solvent interaction energy parameter and the behavior of the chain in various solvents is investigated.
Keywords: Molecular dynamics -- Computer simulation.; Polymers -- Computer simulation.